Research on the resilience of renewable energy in rural areas—Based on the data from Shandong Province - Zihan Ma (PLoS ONE, 2025)
China’s rural energy system faces three challenges: high structural carbonization, low energy utilization efficiency and insufficient supply stability. These systemic contradictions seriously hinder the coordinated promotion of the “dual carbon” strategy and the rural revitalization process. This study takes 16 cities and cities in Shandong Province as the object and combines GIS technology to construct a biomass and solar energy resource evaluation model. The amount of agricultural biomass resources is calculated through the grass valley ratio method. Its resource potential and convertible power generation are quantified, and the “Four Quadrant Model for Renewable Energy Abundance” is introduced to divide regional types. Use spatial analysis to reveal the geographical heterogeneity of resource distribution and explore differentiated low-carbon transformation paths to enhance energy resilience. The study found that the rural renewable energy endowment in Shandong Province showed significant regional differences and proposed four types of development paths: The dual-resource areas jointly develop agricultural and light complementarity and straw power generation, the photovoltaic advantage zone explores energy storage and hydrogen production, the biomass-led areas strengthen cogeneration, and the resource-scarce areas implement green electricity allocation and energy efficiency upgrades. The conclusion shows that multi-energy coordination can improve energy supply stability through space-time complementarity and risk dilution, enhance energy supply resilience, and provide a scientific paradigm for the low-carbon transformation of high-carbon provinces.